Does Europe Have Something to Offer the World? - Alber, Andrus; de Boisgrollier, Nicolas; Kourkoumelis, Dimitris; Stadler, Franz; Micallef, Robert (Tufts Archival Research Center, 2005)
Volume 30, Issue 2. Summer